Development of high-efficient double-layer microwave absorbers based on 3D cabbage-like CoFe2O4 and cauliflower-like polypyrrole. Issue 11 (1st June 2022) - Zhang, Lei; Stalin, N.; Tran, Ngo; Mehrez, Sadok; Badran, Mohamed Fathy; Mohanavel, V.; Xu, Qiang
Abstract: Because of the widespread use of wireless communication and electronic devices, electromagnetic radiation has become a global environmental pollutant. Therefore, finding excellent microwave absorbers (MAs) with appropriate magnetic loss and dielectric loss matching is an urgent assignment. In this work, we successfully fabricated 3D architectures of cabbage-like CoFe2 O4 (CFO) and cauliflower-like polypyrrole (PPy) as MAs. Firstly, the microwave dissipation features of bare CFO and PPy single-layer absorbers were evaluated, which showed no value for effective absorption bandwidth (EAB) and poor values for reflection loss (RL). Then, the microwave dissipation features of double-layer CFO and PPy absorbers were simulated, which showed good values of RL and EAB in the case of CFO as the lower (absorption) layer and PPy as the upper (matching) layer, named as CFO/PPy. Among the CFO/PPy double-layer absorbers, the CFO-1 mm/PPy-1.3 mm showed the best RL of −19 dB and EAB of 3.8 GHz. The real CFO-1 mm/PPy-1.3 mm double-layer absorber was prepared and evaluated for its microwave dissipation features, which showed the RL and EAB values of −17.5 dB and 4.2 GHz, respectively. The real and simulation RL and EAB values were close to each other. In particular, the EAB of the real CFO-1 mm/PPy-1.3 mm could be covered across the whole X band frequency range. The better microwave dissipation features of CFO/PPy double-layer absorbers than the bare CFO and PPy single-layer absorbers could be attributed to better impedance matching capability and coupling interaction between the distinctive layers. Overall, this work provided a new method to manufacture excellent (MAs) for the X band frequency range.